Quality of sleep in women with menopause and its related factors - Ahmady, Fatemeh; Niknami, Maryam; khalesi, Zahra Bostani (Sleep Science, 2022)
BACKGROUND Menopausal period is one of the most critical stages of a womans life. Complications of the menopausal period including sleep disorders can affect the physical and mental state of women. As sleep disorder has a determinant role in the quality of life, this study was conducted to evaluate postmenopausal womens quality of sleep and its related factors.Material and Methods This cross-sectional-analytical study was conducted on 323 postmenopausal women based on convenience and consecutive sampling. The data-gathering tool consisted of two parts; sociodemographic characteristics and the Pittsburgh Sleep Quality Index (PSQI). Data analysis was performed using descriptive and inferential statistical tests at a significance level of p<0.05.Results Sleep disorder was determined in 49.9% of participants. The mean PSQI score was 5.32 ± 3.881. There was a significant correlation between PSQI and age (ß = 0.29, p < 0.001) indicating that sleep disorder increased with an increase in age. There was a significant correlation between body mass index (ß = 0.599, p < 0.001) and undesired sleep quality.Conclusions Regarding the presence of sleep disorder in almost half of the study participants, and the relationship between sleep quality and body mass index and age, it is recommended that decision and policymakers design educational consultation interventions to improve the quality and quantity of sleep in menopause women.
Keywords: Menopause; Women; Sleep; Postmenopause; Dyssomnias